Consumer state dependence, switching costs, and forward-looking producers. A dynamic discrete choice model applied to the diaper market - Dennis Rickert (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This study estimates a dynamic discrete choice model to analyze the effect of switching costs on firm market power. Given the presence of switching costs for consumers in the market for disposable diapers, I show how firms apply dynamic strategies to a market for differentiated products and in a context of vertical retailer-manufacturer relationships. My findings support the existence of state dependence in consumer demand. Furthermore, I show that the firm profits would be higher in a counterfactual scenario of no switching costs.
Keywords: L10; L20; L60; 330